Reaching the Base of the Pyramid: An Analysis of Bakhresa Grain Milling Malawi's Inclusive Business Model - Nagasaki, Tomohiro (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. A growing number of business leaders aspire to raise the well-being of poor populations in the developing world, while also generating profits, by pursuing "inclusive" business models. This thesis offers a description of the inclusive business model pursued by Bakhresa Grain Milling (Malawi) Ltd., and provides an analysis of how this company's outreach among microentrepreneurs (who sell wheat based snacks called mandasi) contributes to its own business success, and how it affects the lives of the entrepreneurs themselves. The research is based on interviews with company personnel, field interviews with microentrepreneurs selling various wheat based products, and secondary household survey data. This thesis suggests that even though the microentrepreneurs are two links in the value chain removed from direct dealings with the company, the company nonetheless recognizes that outreach among them increases the size of its market. While the outreach may increase profits for some microentrepreneurs, it also increases supply and drives down the price of mandasi. It may, therefore, leave some mandasi sellers worse off, while passing on benefits to mandasi consumers, many of whom are part of the base of the pyramid.